The effect of room air cleaners on infection control in day care centres - Ville A. Vartiainen; Johanna Hela; Anni Luoto; Petra Nikuri; Enni Sanmark; Aimo Taipale; Inga Ehder-Gahm; Natalia Lastovets; Piia Sormunen; Ilpo Kulmala; Arto Säämänen (Indoor Environments)
The aim of this study was to assess the effectiveness of air cleaning in reducing the risk of respiratory infection in two day care centres using a simple and robust calculation model. Additionally, we aimed to identify potential hotspots for infections in indoor setting and focus countermeasures accordingly. Initial results from an interventional clinical study are provided as proof-of-concept for the model. We constructed a mathematical model to assess the number of persons at risk for airborne infection transmission in day care. Utilizing the model, we used portable air cleaners in two day care units (A and B, number of children participating in the study n = 43) and compared infection incidents between the two intervention units to the rest of the units in city of Helsinki (n = 607). The intervention buildings had mechanical supply and exhaust air ventilation. The risk modelling suggests that the use of air cleaners reduced the expected number of persons at infection transmission risk significantly. At day care centre A the average reduction was 60% (range 52% - 88%) and at day care centre B 53% (range 14% - 59%). During the approximately six month study period, we observed a significant difference in the days absent from day care due to infections between the intervention and reference day care units. On average, the parents were absent from work due to child’s illness in reference day care centers for 5.53 days and 3.77 days in intervention day care centers during the study period (p=0.009). In relative terms the reduction was approximately 32%. Our study offers compelling evidence to support increasing non-infectious air flow rates in daycare centers during periods requiring infection risk management. This can be implemented with portable air cleaners as an effective and cost-efficient strategy for mitigating the spread of respiratory infections among children. The clinical results support the findings suggested by the theoretical model. Implications and impacts: – Air cleaning seems to be an effective way to reduce infection risk in day cares – Identification of infection risk hotspot will help in desgining the preventive methods – Portable air cleaners offer an affordable and versatile solution also in buildings where existing ventilation is insufficient for infection risk management”